An Advanced Thermal Decomposition Method to Produce Magnetic Nanoparticles with Ultrahigh Heating Efficiency for Systemic Magnetic Hyperthermia (Small Methods 12/2022). Issue 12 (13th December 2022) - Demessie, Ananiya A.; Park, Youngrong; Singh, Prem; Moses, Abraham S.; Korzun, Tetiana; Sabei, Fahad Y.; Albarqi, Hassan A.; Campos, Leonardo; Wyatt, Cory R.; Farsad, Khashayar; Dhagat, Pallavi; Sun, Conroy; et al.
Abstract : Back Cover In article number 2200916, Taratula, Taratula, and co‐workers developed a method for the preparation of cobalt‐doped nanoparticles with a magnetite core and a maghemite shell that exhibit an ultrahigh heating capacity in the presence of an alternating magnetic field (AMF). These nanoparticles, equipped with a cancer‐targeting peptide, accumulate effectively in ovarian cancer tumors after systemic administration at a low dose and elevate the intratumoral temperature up to 50 °C upon exposure to AMF.